Evaluation of E-Government Implementation in Indonesian Local Government (Case Study of the Implementation of Electronic Monitoring and Evaluation in Balangan Local Government) - Erhan, Noviandi (JPAS (Journal of Public Administration Studies), 2017)
The rapid growth of technology has turned the government policies and strategies toward e-government. The e-government somehow believed will enhance the performance of governments. The objectives of this study are to examine the practice of e-government system in Indonesian Local Government. Although Balangan Regency has adopted e-government, however the system is not developed as expected. This research concludes that, critical issues face in the application of e-government in local government is not just technical problems, but more to the management of the system and people awareness. Central government is need to intervene for a better adoption of e-government in local government.